2018
DOI: 10.3389/fphy.2018.00024
|View full text |Cite
|
Sign up to set email alerts
|

Unavowed Abstention Can Overturn Poll Predictions

Serge Galam

Abstract: I revisit the 2017 French Presidential election which opposed the far right National Front candidate Marine Le Pen against the center candidate Emmanuel Macron. While voting intentions for Le Pen stuck below 50% and polls kept predicting her failure, I warned on the emergence of a novel phenomenon I defined as unavowed abstention, which could suddenly reverse the ranking at Le Pen benefit on the voting day. My warning got a massive media coverage. She eventually lost the runoff at a score worse than predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Models of opinion dynamics are among the most studied models of complex systems [1][2][3][4]. This is not surprising, because they can be treated as a zero-level approach to various more complex social processes, including polarization of opinion [5][6][7], diffusion of innovation [8][9][10] or political voting [11][12][13]. In most of these models, public opinion is formed as an outcome from individual opinions of mutually interacting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Models of opinion dynamics are among the most studied models of complex systems [1][2][3][4]. This is not surprising, because they can be treated as a zero-level approach to various more complex social processes, including polarization of opinion [5][6][7], diffusion of innovation [8][9][10] or political voting [11][12][13]. In most of these models, public opinion is formed as an outcome from individual opinions of mutually interacting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Second, effective turnout accounts for invalid votes (i.e., blank and null votes) when calculating turnout: it is measured as the number of valid votes divided by the total number of registered voters. This differentiated operationalization of electoral participation into overall and effective turnout follows recent relevant work (see, e.g., Barnes and Rangel 2018 ; and Galam 2018 for French elections). Distinguishing between overall and effective turnout is particularly pertinent when comparing paper versus Internet voting, as the use of voting machines constitutes an effective method for reducing voter errors and uncounted ballots (Alvarez and Hall 2008 ; Germann 2020 ).…”
Section: Methodsmentioning
confidence: 67%
“…Socio-physical models based on classical physical effects [44,45,49,63,71,103,104] have become an important topic of mainstream scientific research and have found practical applications outside academia [105,106]. Thus, one of the main questions of this paper is what, in general, makes a quantum-mechanical model attractive for the analysis of opinion polarisation in social networks.…”
Section: The Origin Of Quantum Advantage In Models Of Social Mediamentioning
confidence: 98%